Close Collaboration with Parents intervention improves family-centered care in different neonatal unit contexts: a pre-post study - Mirka Toivonen; Liisa Lehtonen; Eliisa Löyttyniemi; Sari Ahlqvist-Björkroth; Anna Axelin (NATURE PUBLISHING GROUP, 2022)
Background
The quality of family-centered care and parental participation in care in neonatal units differ widely across the world. Appropriate education might be an effective way to support medical staff in neonatal units to collaborate with parents and implement family-centered care. The aim of this study was to evaluate the effects of the educational intervention on the quality of family-centered care in eight Finnish neonatal intensive care units from both the staff and parent perspectives.
Methods
A mixed-method pre-post intervention study was conducted in eight neonatal intensive care units in Finland. Data were collected from staff and parents using the Bliss Baby Charter audit tool and semi-structured interviews. Results The quality of family-centered care, as assessed by staff and parents, increased significantly after the intervention in all eight units. The intervention was able to help staff define and apply elements of family-centered care, such as shared decision making and collaboration between parents and staff. In interviews, staff described that they learned to support and trust the parents' ability to take care of their infant.
Conclusions
The educational intervention increased the quality of family-centered care and enabled mutual partnership between parents and staff.
Impact
This study shows that the educational intervention for the whole multi-professional staff of the neonatal unit improved the quality of family-centered care. The Close Collaboration with Parents intervention enabled mutual partnership between parents and staff. It also provides evidence that during The Close Collaboration with Parents intervention staff learned to trust the parents' ability to take care of their infant.